Baccharis trimera (Less.) DC responses to water restriction - Nava, Francine Falcão de Macedo; Luz, Vilson Conrado da; Stempkowski, Lucas Antonio; Gotz, Lenir Fátima; Tonial, Fabiana; Cargnelutti, Denise (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Climate change can cause imbalances in plants. Baccharis trimera is a specie usually found in harsh conditions and has medicinal and agricultural properties. Thus, this study aimed to evaluate the biochemical and physiological responses of this plant under water restriction (WR) levels. B. trimera samples were identified and collected in Erechim/RS and propagated in a greenhouse. When acclimated, they were subjected to 0, 25, 75 and 100% WR, determined according to the water saturation in the soil by capillary action. After 30 days of treatment, the physiological responses: growth, and fresh and dry biomass; and the biochemical responses: activity of superoxide dismutase (SOD), guaiacol peroxidase (GP) and ascorbate peroxidase (APX) enzymes, proline, protein and hydrogen peroxide content, and lipid peroxidation, were determined. Data were submitted to regression analysis and Pearson correlation. The WR of 27.37%, on average, induced an increase in physiological parameters, but the root growth was impaired in conditions above 50% of WR. With the increase in WR there was an increase in the activity of SOD in the shoot and APX in the root. In low WR conditions, proline contents were maintained. Therefore, with low levels of WR, around 27%, B. trimera has increase in root growth and root and shoot biomass. Proline, and SOD and APX activity are a pathway that scavenging the stress generated by WR on B. trimera.